Situation Report: Romania, 22 February 1971 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Decree on the Training of Party and State Cadres Party Strength and Structure Radio and Television Committee Chairman Replaced Draft Bill on Foreign Trade Trade Agreements with Communist China Comments on Warsaw Pact Foreign Ministers' Conference Romania Literara Round-Table on "The Social Element in Literature"